EMOTIONAL INTELLIGENCE AND ACQUISITION OF ENGLISH LANGUAGE ORAL COMMUNICATION SKILLS - Tetiana Andrienko; Nataliia Chumak; Vlad Genin (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2020)
Studying the factors of successful acquisition of ESL speaking skills in Ukrainian adult learners, the authors focused on the correlation between emotional intelligence and development of oral communication skills, and, on the other hand, on the growth of these indicators as a result of purposeful inclusion of content-related emotions into activities aimed at the development of speaking and listening skills. Theoretically based on the ideas of emotional intelligence as an important factor in human interaction and guided by the hypothesis that content-related emotions intensify emotional involvement and have a positive influence on the acquisition of oral communication skills, the researchers applied Mayer-Salovey-Caruso Emotional Intelligence Test and the English Language Oral Communication Skills Test developed by the authors, to measure the key oral communication skills indicators against a 100 point scale. Experimental teaching of 124 undergraduate students of International Relations during September 2018 - May 2019 proved a beneficial influence of including emotions in the learning activities on the acquisition of ESL oral communication skills, as well as on student motivation and overall quality of student experiences. Significant increments in Emotional Intelligence and ESL oral communication skills in the experimental group compared to insignificant growth of the same indicators in the Reference group allow to establish a positive correlation between the growth of emotional intelligence and acquisition of the ESL speaking skills pursuant to inclusion of content-related emotions into the ESL learning in Ukrainian students.